METHOD FOR MANUFACTURING ZnSb-BASED THERMOELECTRIC MATERIAL (Scientific journal of the Fergana State University, 2025)
In this article, a mixture of ZnSb semiconductor particles, ground to a powder state, is prepared using 70% ethyl alcohol, and they are placed on a heat-resistant substrate with an internal diameter of 1 mm, for example, a ceramic tube, and pressed together on both sides with metal rods acting as ohmic contacts. Then, by heating and bonding the particles at temperatures close to the melting temperature of the ZnSb compound, T=400-600 ℃, a rod-shaped ZnSb polycrystal with a diameter of 1 mm is formed. The rod resistance of the ZnSb semiconductor in a polycrystalline structure is R≤1 kOhm, and tunnel contacts and local energy levels are formed in its intergranular boundary regions, in which energy levels ensure resonant tunneling of electrons.